DETERMINATION OF THE PSYCHO-EMOTIONAL STATE OF STUDENTS OF 2-ND YEAR STUDENTS OF IVANO-FRANKIVSK NATIONAL MEDICAL UNIVERSITY DURING DISTANCE LEARNING BASED ON A QUESTIONNAIRE - V. M. Fedorak; O. R. Ivantsiv; I. I. Bilinskyi; V. V.Fedorak (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
One of today’s important problems is the Covid-19 pandemic, which has caused a disturbance in people’s lives, in particular among stu-dents. As a result, students of universities were transferred to distance learn-ing. The problem of studying is the psycho-emotional state of students in the conditions of distance learning, somatic and behavioural manifestations of anxiety has become rele- vant to us. Aim: to assess the psycho-emotional state, somatic and behavioural mani- fes-tations of anxiety in medical students during the period of distance learning. Methods. 76 students of the 2nd year studying were interviewed by means of an anonymous questionnaire.. An online questionnaire based on Google-Forms was used for the examination, which included questions to identify psycho-emo- tional and somatic manifestations of anxiety. In order to achieve the objective, the following tasks were set: identify the emotional and behavioural reactions of students and investigate the somatic manifestations of anxiety using the developed questionnaires. Based on analysis of questionnaire responses, we found that the worldwide Covid-19 pandemic is a significant social factor affecting the func-tioning of the body and behavioural responses of students, but most of them have learned to control their emotions and behaviours. Only 19.7% of re-spondents reported an increase of negative emotions in daily life during dis-tance learning, while 40.8% reported a de- creased interest in distance learning compared to live learning, and frequent feeling of anxiety and apathy. The emotional state of about 25% of the partici- pants decreased during the period of distance learning. After studying the manifestations of anxiety at the somatic level, we found that most of the students didn’t show signs of somatic manifestations of anxiety, 63.2% of students never felt dizziness or headache during the period of dis-tance learning, 75% of students never felt tremor. In fact, 71.1% of them never expe- rienced an increase in heart rate or arterial blood pressure during dis-tance learning, but most of the respondents (56.6%) often feel tired or drowsy during distance learning. Сonclusion. Our research has show that the worldwide pandemic has a sig-nificant impact on the functioning of the body and behavioural reactions of students. However, during the period of distance learning, students have de- veloped the resistance to stress and have the ability to respond appropriately to the social challenges facing humanity beginning in 2019. Key words: distance learning, students, psycho-emotional state, a ques-tionnaire.